UPAYA PENINGKATAN MUTU MENGAJAR GURU MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH DI SMA NEGERI 1 TONGAS PROBOLINGGO - Taufiq Surya Hadi (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
This study aims to analyze efforts to improve the teaching quality of teachers through the academic supervision of the principal at SMA Negeri 1 Tongas Probolinggo. This study used descriptive qualitative method. The research was conducted at SMA Negeri 1 Tongas Probolinggo in 2020. The results of the study concluded that the academic supervision implementation system for the Principal of SMA Negeri 1 Tongas Probolinggo has formed a team of supervisors or a Teacher Performance Assessment Team. The Principal has planned an academic supervision program, requested a report from the supervisor, and followed up on the results of the supervision as appropriate. The teaching quality of teachers at SMA Negeri 1 Tongas Probolinggo has improved in terms of administration and process. The implementation of continuous and well-programmed supervision has a major role in improving the quality of teacher teaching. The factors that support the implementation of the academic supervision of the Principal of SMA Negeri 1 Tongas Probolinggo are the high professionalism of the principal, high competence of supervisors (PKG team members), teachers who are on average ready to be supervised by the Principal.